Molecular characterisation of Aspergillus flavus isolates from peanut fields in India using AFLP - Singh,Diwakar (2015)
Aflatoxin contamination of peanut, due to infection by Aspergillus flavus, is a major problem of rain-fed agriculture in India. In the present study, molecular characterisation of 187 Aspergillus flavus isolates, which were sampled from the peanut fields of Gujarat state in India, was performed using AFLP markers. On a pooled cluster analysis, the markers could successfully discriminate among the ‘A’, ‘B’ and ‘G’ group A. flavus isolates. PCoA analysis also showed equivalent results to the cluster analysis. Most of the isolates from one district could be clustered together, which indicated genetic similarity among the isolates. Further, a lot of genetic variability was observed within a district and within a group. The results of AMOVA test revealed that the variance within a population (84%) was more than that between two populations (16%). The isolates, when tested by indirect competitive ELISA, showed about 68.5% of them to be atoxigenic. Composite analysis between the aflatoxin production and AFLP data was found to be ineffective in separating the isolate types by aflatoxigenicity. Certain unique fragments, with respect to individual isolates, were also identified that may be used for development of SCAR marker to aid in rapid and precise identification of isolates.